2021
DOI: 10.17582/journal.pjar/2021/34.1.218.226
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Drying Process of Rambutan by Combined Method of Osmosis Ultrasound and Complementary Drying of Hot Air

Abstract: D rying of fruits has been considered as a way to improve the durability, and is one of the main methods which have been common for centuries. Unlike fresh vegetables which are kept only for a short period of time and in special circumstances, dried products can be kept a long time without reducing the nutritional value. Also, because of the low mass weight of dried fruits, they are easily and conveniently transported (Da Silva et al., 2017). The fruit used in this research for drying is Rambutan which is nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The rehydration ratio of kiwifruit slices reduced from 204.1% to 158.8%, by increasing sucrose concentration from 20 to 40%. Similarly, Farooq, et al 32 reported that the rehydration ratio of Rambutan decreased with increasing osmotic solution concentration. Shekar and Javadi 33 observed a decrease in rehydration rate when using UAOD compared to control samples, and observed a greater reduction in UAOD samples than in osmotically dehydrated samples.…”
Section: Resultsmentioning
confidence: 85%
“…The rehydration ratio of kiwifruit slices reduced from 204.1% to 158.8%, by increasing sucrose concentration from 20 to 40%. Similarly, Farooq, et al 32 reported that the rehydration ratio of Rambutan decreased with increasing osmotic solution concentration. Shekar and Javadi 33 observed a decrease in rehydration rate when using UAOD compared to control samples, and observed a greater reduction in UAOD samples than in osmotically dehydrated samples.…”
Section: Resultsmentioning
confidence: 85%